Provision Of A Mandatory Will For Adopted Children Who Are Not Adopted Through Court Determination Based On The Maqashid Syariah Perspective: (Case Study of Palembang High Religious Court Decision Number. 35/Pdt.G/2018/PTA.Plg) - Febry Larasati; Nur Chanifah; Herlindah Herlindah (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Marriage itself has a goal, namely to form a happy family, and hopes that children will be the pride of the family so that they can continue their offspring. However, it can be seen that there are still many marriages that do not produce offspring. So many of these husband and wife couples adopt children. To anticipate conflicts or disputes in the future, child registration should also be done through a court order, this is to ensure legal certainty. As an example of the case in decision No. 35/Pdt.G/2018/PTA.Plg. The case in this decision is that there was an adopted child named Kiki Wahyuni who was not adopted through a court decision, but only adopted through custom. This of course gave rise to conflict. When both of her adoptive parents died, the research results showed that even though Kiki Wahyuni was not adopted through a court decision, However, the judge brought witnesses to state that it was true that Kiki Wahyuni had been cared for since she was a 1 (one) year old baby, namely around 1989 to 1999. Based on the Compilation of Islamic Law, Kiki Wahyuni should not have received assets from her late adoptive parents through a mandatory will. However, because there is a conflict between Article 171 letter h of the Compilation of Islamic Law and the court's decision, then through the principle of Res Judicata Pro Viratate Habetur, the judge's decision is considered correct and can be implemented